Archive Management and Archive Arrangement in the Finance Division (Education Office of Medan City Government) - Riska Nasution; Zuhrinal M Nawawi (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
This study aims to determine the management of incomingand outgoing letters and arrangements, especially in the Medan City Education Office. The results showed that the management of incoming and outgoing letters at the Medan City Government Education Office, especially in the financial room, was still not carried out optimally, which was caused by: 1) limited equipment for storing letters or documents, especially filing cabinets; 2) limited letter storage space so that the continuous increase in the volume of letters resulted in the available storage space and equipment unable to accommodate letters.